Microdialysis to Quantify Inflammatory Cytokines in the Glenohumeral Joint: A Brief Methods Report. (May 2019) - Hogaboom, Nathan S.; Onishi, Kentaro; Worobey, Lynn A.; Boninger, Michael L.
Abstract : Abstract: Microdialysis quantifies in vivo soft-tissue biochemical concentrations via passive diffusion of interstitial molecules through a porous membrane into a dialysate. The purpose of this pilot study was to evaluate a technique to measure inflammatory cytokines associated with rotator cuff tendinopathy by inserting a microdialysis catheter into the posterior glenohumeral joint. The technique was tested in a convenience sample of six pain-free, able-bodied veterans. Complete dialysate samples were collected in two participants. Two participants' sample volumes were smaller than what was required for analysis (30 μl) and thus were diluted. Catheter failures in two participants prevented collection altogether. Three cytokine concentrations were quantified: interleukin-1 receptor antagonist, interleukin 8, and regulated on activation, normal T-cell expressed and secreted. Microdialysis is not recommended for use in the glenohumeral joint, yet quantification of glenohumeral joint cytokines could yield valuable information to better understand pathophysiology of the joint and its surrounding tissues. Another technique, such as joint lavage, may be a more attractive alternative to overcome the limitations of microdialysis in the glenohumeral joint. Abstract : Supplemental digital content is available in the text.